Respuesta :

Answer:

y = [tex]\frac{-7}{4}e^{\frac{-1}{2}x}+ \frac{11}{4}e^{\frac{3}{2}x}[/tex]

Step-by-step explanation:

Given:

4y" – 4y' – 3y = 0, y(0) = 1, y'(0) = 5

Now,

The auxiliary equation will be given as:

4m² - 4m - 3 = 0

or

4m² + 2m - 6m - 3 = 0

or

2m (2 + 1) - 3 (2m + 1) = 0

or

( 2m - 3 ) × ( 2m + 1 ) = 0

therefore,

m = [tex]\frac{\textup{3}}{\textup{2}}[/tex] and m = [tex]\frac{\textup{-1}}{\textup{2}}[/tex]

thus,

the general equation comes as:

y = [tex]C_1e^{mx}+ C_2e^{mx}[/tex]

or

y = [tex]C_1e^{\frac{-1}{2}x}+ C_2e^{\frac{3}{2}x}[/tex]

now,

at y(0) = 1

therefore,

1 = [tex]C_1e^{\frac{-1}{2}\times0}+ C_2e^{\frac{3}{2}\times0}[/tex]

or

C₁ + C₂ = 1  .............(1)

and,

y' = [tex]\frac{-1}{2}C_1e^{\frac{-1}{2}x}+ \frac{3}{2}C_2e^{\frac{3}{2}x}[/tex]

also,

y'(0) = 5

thus,

5 = [tex]\frac{-1}{2}C_1e^{\frac{-1}{2}\times0}+ \frac{3}{2}C_2e^{\frac{3}{2}\times0}[/tex]

or

3C₂ - C₁ = 10 ...........(2)

on adding 1 and 2, we get

     C₁ + C₂ = 1

+ (- C₁ + 3C₂) = 10

===============

4C₂ = 11

or

C₂ = [tex]\frac{\textup{11}}{\textup{4}}[/tex]

thus,

   C₁ + C₂ = 1

or

   C₁ + [tex]\frac{\textup{11}}{\textup{4}}[/tex]  = 1

or

C₁ =  [tex]\frac{\textup{-7}}{\textup{4}}[/tex]

Hence,

The solution is y = [tex]C_1e^{mx}+ C_2e^{mx}[/tex]

on substituting the values,

y = [tex]\frac{-7}{4}e^{\frac{-1}{2}x}+ \frac{11}{4}e^{\frac{3}{2}x}[/tex]

Solving the characteristic equation and applying the initial conditions, the solution of the IVP is:

[tex]y(t) = -1.75e^{-0.5t} + 2.75e^{1.5t}[/tex]

The IVP is given by:

[tex]4y^{\prime\prime} - 4y^{\prime} - 3y = 0[/tex]

The characteristic equation is:

[tex]4r^2 - 4r - 3 = 0[/tex]

Which is a quadratic equation with coefficients [tex]a = 4, b = -4, c = -3[/tex], and thus:

[tex]\Delta = b^2 - 4ac = (-4)^2 - 4(4)(-3) = 64[/tex]

[tex]x_1 = \frac{-b - \sqrt{\Delta}}{2a} = \frac{4 - 8}{8} = -0.5[/tex]

[tex]x_2 = \frac{-b - \sqrt{\Delta}}{2a} = \frac{4 + 8}{8} = 1.5[/tex]

Thus, the solution is in the format:

[tex]y(t) = ae^{-0.5t} + be^{1.5t}[/tex]

Applying the initial conditions:

[tex]y(0) = 1 \rightarrow a + b = 1[/tex]

[tex]y^{\prime}(0) = 5 \rightarrow -0.5a + 1.5b = 5[/tex]

From the first equation, [tex]a = 1 - b[/tex], and replacing in the second:

[tex]-0.5a + 1.5b = 5[/tex]

[tex]-0.5 + 0.5b + 1.5b = 5[/tex]

[tex]2b = 5.5[/tex]

[tex]b = \frac{5.5}{2}[/tex]

[tex]b = 2.75[/tex]

[tex]a = 1 - b = 1 - 2.75 = -1.75[/tex]

Then, the solution to the IVP is:

[tex]y(t) = -1.75e^{-0.5t} + 2.75e^{1.5t}[/tex]

A similar problem is given at https://brainly.com/question/13260929

Otras preguntas